Evaluasi Daya Dukung Lahan Permukiman di Kecamatan Sirimau Kota Ambon Menggunakan Teknik Penginderaan Jauh dan GIS - Lasaiba, Mohammad Amin (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2024)
Developing settlements require adequate land to meet housing needs. However, significant challenges arise from rapid population growth and ongoing urbanization, making it difficult to maintain sufficient land-carrying capacity for the local population's sustainability and quality of life. This study analyses the land carrying capacity and settlement development in Sirimau District, Ambon City. The data collection methods include observations and documentation from secondary sources such as government reports and geospatial data. The analysis was conducted using time series satellite imagery from 2012 and 2022 and the nearest neighbour analysis method with ArcGIS and the Average Nearest Neighbor tool. The study's results indicate that the calculation of land carrying capacity shows an average decline in settlements' land carrying capacity. In 2022, Ahusen, Rijali, and Galala villages recorded a decrease in land carrying capacity, making them unable to accommodate the resident population. Population pressure and settlement growth have negatively impacted land carrying capacity. Significant settlement development occurred in Batu Merah and Soya villages, with a "clustered" settlement distribution pattern. The conclusions of this study emphasize the need to raise awareness and understanding of Regional Spatial Planning (RTRW) to achieve sustainable settlement development. An integrated effort from the government, community, and developers is required to optimize land use and maintain the ecological carrying capacity in Sirimau District.